Efektivitas Senyawa Bioaktif Ekstrak Kencur (Keampferia galanga Linn) Menggunakan Berbagai Metode Ekstraksi - Primawati, Sri Novita (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2015)
The secondary metabolite content of Keampferia galanga i.e essential oil, sesquiterpenoid, flavonoid, fenolic compound, and alkaloid were used as an antibacterial agent. The aimed of this research were to isolated Keampferia galanga’s anti bacterial compound using various extraction methods i.e stew, infuse, and maseration using ethanol as solvent. The research was laboratory experimental and designed using completely randomized method with 75 μl volume extract and 3X repetition. The antibacterial activity test were used wall diffusion methods. The inhibition zone were tabulated and analyzed using one way analysis of variance (ANAVA). The result showed that there were signifant differences on S. typhimurium growth between stew, infuse, and maseration methods on 5 % significant level, but the the inhibition zone were weak (less than 15 mm in diameter). So it can be concluded that the maseration method using ethanol as a solvent showed weak inhibition activity on S. typhimurium growth.